COMPARISON OF SURFACE RADIATION DOSE TO THE GONADS BY RADIOGRAPHIC EXAMINATION OF THE LUMBAR SPINE USING COMPUTED RADIOGRAPHY AND DIRECT DIGITAL RADIOGRAPHY - Priyanka; Kotian, Rahul P; Panakkal, Nitika C (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The objectives are aimed to study the comparison of SRD to the gonads by radiographic examination of the lumbar spine using computed radiography (CR) and direct digital radiography (DR) and to evaluate dose differences according to gender. Methods: A total of 120 subjects with an equal number of males and females referred for lumbar spine anteroposterior (AP) and lateral was included in the study. Sixty patients had undergone X-ray in CR X-ray unit and 60 in DR X-ray unit. SRD to gonads from a radiographic examination of the lumbar spine was measured in CR and DR using Mult-O-Meter, and obtained value of SRD was in μGy. Statistical analysis was performed using Statistical Package for the Social Sciences. Data were represented as a median and interquartile range. Mann–Whitney U-test was used for the comparison of SRD to gonads. Two-way analysis of variance (ANOVA) test was used to find out the statistically significant difference in SRD to the gonads according to gender from radiography of lumbar spine taken using CR and direct DR. Results: There was a statistically significant difference in SRD to gonads from radiography of lumbar spine AP and lateral taken using CR and direct DR (p<0.001). There was no statistically significant difference in SRD to the gonads in males and females from radiography of lumbar spine AP (p=0.577) and lateral (p=0.164) taken using CR and direct DR. Conclusion: It was found that SRD to gonads from lumbar spine AP was 54% lower in direct DR and SRD to gonads from lumbar spine lateral was 68% lower in direct DR than CR.